2014
DOI: 10.1038/jid.2013.403
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cells Regulate Allergic Contact Dermatitis by Modulating CCR2–Dependent TNF/iNOS–Expressing Ly6C + CD11b + Monocytic Cells

Abstract: Monocytes and their derived cells have critical roles in inflammation and immune defense. However, their function in skin diseases such as allergic contact dermatitis remains poorly defined. Using a model of contact hypersensitivity (CHS) toward 2,4-dinitrochlorobenzene, we show that Ly6C+ CD11b+ monocytic cells participate in the pathophysiology of CHS and their accumulation is regulated by effector CD8 T cells. These Ly6C+ CD11b+ monocytic cells are the primary contributors of tumor necrosis factor-α (TNF-α)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 58 publications
(79 reference statements)
0
16
1
Order By: Relevance
“…We speculated that tight contact among monocytes in the clusters provided a microenvironment for accelerating monocyte activation in situ. Although previous studies have shown that IFN-g modulates myeloid cell infiltration and stimulates their activation (Chong et al, 2014), our results showed that mobilizing the formation of monocyte clusters represents another pathway leading to the stimulation of monocyte activation in addition to direct stimulation by IFN-g.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…We speculated that tight contact among monocytes in the clusters provided a microenvironment for accelerating monocyte activation in situ. Although previous studies have shown that IFN-g modulates myeloid cell infiltration and stimulates their activation (Chong et al, 2014), our results showed that mobilizing the formation of monocyte clusters represents another pathway leading to the stimulation of monocyte activation in addition to direct stimulation by IFN-g.…”
Section: Discussioncontrasting
confidence: 83%
“…CCR8 has been reported to mediate inflammatory monocyte migration into lymph nodes, and CCR6 has been reported to contribute to monocyte-derived dendritic cell (DC) migration toward the epithelium (Le Borgne et al, 2006;Qu et al, 2004). In the challenge phase of CHS, CCR2 mediates inflammatory monocyte infiltration into the dermis (Chong et al, 2014). However, it remains unclear how interstitial monocytes are guided to inflammatory foci.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1, despite the differences associated with induced immune responses 9 these models share logistically similar strategies (overlaid on model-specific timelines). These similarities include a sensitization phase of toxicant exposure to a shaved region of a dorsal flank prior to the application of toxicant to the same mouse later in the protocol to the experimental (left) ear (control contralateral right ears were exposed to vehicle alone (olive oil:acetone (4:1)).…”
Section: Resultsmentioning
confidence: 99%
“…Mixed Th1/Th17 and Th2 cellular responses characterized by the production of IL-2, IFN-γ, and IL-17 are prevalent responses linked with the inflammation and injury associated with many toxicant contact hypersensitivity reactions see for example 7 . For example, epicutaneous sensitization by haptens such as dinitrofluorobenzene (DNFB 8 ), dinitrochlorobenzene (DNCB 9 ), or certain metals (e.g., Nickel 10 ) induce contact hypersensitivity reactions characterized by acute inflammatory and Th1 responses that are accompanied by skin inflammatory infiltrates often dominated by activated T lymphocytes, monocytes, and increased numbers of neutrophils. In contrast, other toxicants such as trimellitic anhydride (TMA 11 ) represent non-classical contact allergens that elicit the production of Th2 cytokines such as IL-4, IL-5, and IL-13.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, an increase in the generation of in ammatory cytokines, such as IL-6, IL-17 and COX-2, can lead to a chain reaction of in ammation [42][43][44]. TNF-α and IL-17 are important markers of skin in ammation, and the inhibition of in ammatory cytokines, such as TNF-α and IL-17, yields positive effects on the treatment of dermatitis [45][46][47][48]. Additionally, PI3K/mTOR/Akt inhibitors are known to act as therapies for in ammatory skin diseases, such as skin atrophy [49].…”
Section: Discussionmentioning
confidence: 99%